Tracing the Weaknesses of the Regulatory Framework for Clinical Trial in Nigeria - Salihu, Sani Ibrahim; Yusof, Yuhanif; Halim, Rohizan (Center for Sustainabality Research & Consultancy, 2015)
Nigeria is one of the developing countries with a very weak and incomprehensive regulatory framework for clinical trials. Past abuses of human subjects in clinical trials and cases of negligence and outright fraud necessitate the need for a stronger legal framework. An outbreak of meningitis in Nigeria in 1996 led to clinical trial of Trovan Drugs by Pfizer, which left many of the research subjects seriously impaired. Some died while some suffered paralysis and brain damage. It was obvious Nigeria has a weak regulatory frame work from the incident that took place in the mentioned above at the Infectious Dieses Hospital (IDH) Kano. Available literatures have also shown that at the time of the trial in Kano, there was no ethics committee to ensure ethics review process and monitor the ongoing trial. Objectives: This research aimed at examining the Nigerian regulatory framework to bring out its weaknesses. It will also examine the strength and weakness of the current regulatory agencies, and suggest better regulatory framework that will make Nigerians less vulnerable to manipulation and fraud in clinical trials. Methodology: Library research is used to study both primary and secondary legal resources. Finding: Lack of standard regulatory body and lack unified legal framework is the cause of failure to protect human subject in Nigeria